Multicultural Education; An Effort To Build Harmony In Diversity In Elementary Schools - Jajat, Jajat Darojat; Somantri (Journal of Asian Primary Education (JoAPE), 2025)
Indonesia is a country with high diversity that includes ethnicity, religion, culture, language, and socio-economic background. This diversity is clearly reflected in the primary school environment, which is the initial stage of children's character building. However, if not managed properly, diversity can lead to social conflicts such as intolerance and discrimination. Therefore, multicultural education becomes a strategic approach in instilling the values of tolerance, mutual respect and empathy from an early age. This education not only introduces students to diversity, but also guides them to understand and respect differences as social wealth. Integrating multicultural values into the basic curriculum can strengthen inclusive attitudes and create a learning environment that is friendly to all differences. The role of teachers, schools, as well as support from parents and communities is crucial in building an inclusive atmosphere in primary schools. Through this approach, primary education can produce a generation that is not only academically intelligent, but also has high social intelligence and is ready to live peacefully in a pluralistic and global society.